Psychometric Properties of a Scale to Assess Parental Self-Efficacy for Influencing Children's Dietary, Physical Activity, Sedentary, and Screen Time Behaviors in Disadvantaged Areas. (February 2018) - Norman, Åsa; Bohman, Benjamin; Nyberg, Gisela; Schäfer Elinder, Liselotte
Background . According to social cognitive theory, self-efficacy is central to behavior change. Consequently, parental self-efficacy (PSE) for influencing children's dietary, physical activity (PA), sedentary, and screen time behaviors is important for child obesity prevention. The aim of this study was to evaluate the psychometric properties of an instrument to measure PSE regarding these behaviors in disadvantaged areas. Method . Parents ( n = 229) of whom 47% had completed secondary school or less, and who participated in the Healthy School Start trial, responded to a 15-item PSE instrument. Children's diet and screen time were measured through parent reports. PA and sedentary behaviors were measured using accelerometers. Construct validity was assessed using exploratory factor analysis (EFA), criterion validity by correlations with child behaviors, and internal consistency by Cronbach's alpha. Results . The EFA yielded three factors: (a) PSE for promoting PA; (b) PSE for limiting intake of unhealthy foods, unhealthy drinks, and screen time; and (c) PSE for promoting intake of fruits and vegetables, all with acceptable to good internal consistency (α = .77-.81). Significant correlations ( p < .01) were found between children's dietary ( r s = −.19 to −.29) and screen time ( r = −.29) behaviors and Factor 2, and dietary behaviors and Factor 3 ( r s = .20-.39) but not regarding PA and sedentary behaviors and Factor 1. Conclusion . The instrument demonstrated good construct validity and acceptable to good internal consistency regarding all but PA behaviors. It may be useful for assessing PSE in child obesity prevention interventions in disadvantaged settings after some refinement.